2021
DOI: 10.1109/access.2021.3094334
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Machine Learning Framework for Stress Prediction via Sensor Integrated Keyboard Data

Abstract: Today's sedentary life leads to a plethora of lifestyle-related illnesses. This has led to the quest to predict diseases before they occur. In the past, research on stress prediction was carried out conventionally in a laboratory-based environment. However, recent studies are focusing on developing noninvasive ways to predict stress with the help of wearable devices. Generally, the models developed for stress prediction do not provide accurate results because the stress patterns are highly subjective and vary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The future work of this study is to suggest an edge-based data processing system to bring computation and data storage closer to the patient's location to improve emergency services response time and save bandwidth in the system ( 20 ). In this research ( 21 ), the authors have investigated the effects of stress and for this purpose they used the sensor data from the accelerometer and gyroscope on smart phones. The authors monitored the writing behavior of 46 participants on the touchscreen panel of smart phones.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The future work of this study is to suggest an edge-based data processing system to bring computation and data storage closer to the patient's location to improve emergency services response time and save bandwidth in the system ( 20 ). In this research ( 21 ), the authors have investigated the effects of stress and for this purpose they used the sensor data from the accelerometer and gyroscope on smart phones. The authors monitored the writing behavior of 46 participants on the touchscreen panel of smart phones.…”
Section: Related Workmentioning
confidence: 99%
“…The authors applied a range of classification algorithms on these features such as Decision Trees, Bayesian Networks and k-Nearest Neighbor methods. The authors observed that the accuracy of these classifiers was 74.26, 67.86, and 87.56% respectively ( 21 ). In paper ( 22 ) discusses applicability of Intelligent IoT based on Collaborative Machine Learning in healthcare and medicine by presenting a holistic multi-layer architecture.…”
Section: Related Workmentioning
confidence: 99%